Service quality and behavioural intentions in broadband services selection. Issue 4 (27th May 2014) - Sabbir Rahman, Muhammad; Nusrate Aziz, Md.
Abstract : Purpose: – The purpose of this paper is to examine consumers' perceptions and their behavioural intentions in selecting an internet broadband service in Malaysia by inspecting young users' perceptions, in respect of the technical, functional and experience economy perspective. Design/methodology/approach: – A survey methodology using questionnaires was adopted to solicit the required information from 400 existing, as well as potential users. Data were analysed through exploratory factor analysis, confirmatory factor analysis and structural equation modelling. Findings: – The research shows that in selecting an operator's service both technical and functional qualities are highly mediated by young consumers' perceptions in explaining their behavioural intentions. The paper also finds that the experience economy variable has a direct effect, which is more dominant on young consumers' behavioural intentions than the indirect effect through perception, which implies a partial mediation. Research limitations/implications: – The study focused on young users' perceptions and the implicative behavioural intentions in selecting a broadband operator within the Klang Valley area in Malaysia. Thus, it may not be generalized to all young consumers' around the world. Practical implications: – This study identifies the perceived attributes of quality and experience economy as well as generalizing the young consumers' buying intentions in selecting an internet broadband operator in Malaysia. Originality/value: – This research contributes to the existing literature because the study of the behavioural aspects of young consumers is of great importance for marketers to identify the consumers' ultimate choice in internet broadband selection in Malaysia.